Characterization of A Directional Coupler Waveguides Five Layers based on A Variation of The Electric Field in Two Border Area - Wati, Farida; Rohedi, Ali Yunus; Pramono, Yono Hadi (IPTEK Journal of Proceedings Series, 2014)
Will be Analized the Effective Refractive Indeks with Electric Field Variations In Two Border Areas Layers To Design Vaweguide five layers, where the dispersion relation equation is getting through from the field equations in waveguides five layers. Wave guide five layer nonlinear structure is one of wave guide structure usually used model on design medium laser MQM and system path on device integrated optic. The composition consist of five layer usually used was L-NL-L-NL-L when L and LN as linear and non linear respectively. Will specifically examined the role of the Jacobian elliptic function Cn and Sn in the formulation of the dispersion relation to determine the type of guided modes in a nonlinear waveguide structure of five layers, which are based on the effective refractive index relation to the variation of the electric field at the boundary of two media waveguide region. There are 3 types of guided modes, namely mode symmetry, asymmetry, and antisimentri. The greater the effective refractive index is given, allowing more conditions for the value of the electric field . The dispersion equation shows a very flexible and general expression because it can be applied to the waveguides multilayer having symmetric or asymmetric structures